PERBANDINGAN NILAI NIHSS ANTARA PASIEN STROKE ISKEMIK AKUT YANG MEMILIKI KADAR MAGNESIUM SERUM RENTANG NORMAL BAWAH DENGAN RENTANG NORMAL ATAS - Moch Syahrial Pramudia, Herainy Hartono (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION MAGNESIUM MG PLAYS AN IMPORTANT ROLE IN MOLECULAR PATHOGENESIS OF ISCHEMIC STROKE MG COULD FUNCTIONS AS NEUROPROTECTOR OF FREE RADICALS THEREFORE IT WILL REDUCE NEURONAL CELL DEATH DUE TO ISCHEMIC CASCADE AND PRODUCE BETTER NIHSS OUTCOME